Cognitive Remediation in Middle-Aged or Older Inpatients with Chronic Schizophrenia: A Randomized Controlled Trial in Korea - Choi, Kee-Hong; Kang, Jinsook; Kim, Sun-Min; Lee, Seung-Hwan; Park, Seon-Cheol; Lee, Won-Hye; Choi, Sun; Park, Kiho; Hwang, Tae-Yeon (Frontiers in Psychology, 2018)
BBackground. Accumulating evidence indicates that cognitive remediation (CR) is effective for improving various cognitive deficits in adult patients with schizophrenia. Although reports of brain plasticity in older adults and the service needs for chronic patients with schizophrenia are increasing, very few randomized controlled trials of CR have been conducted in middle-aged or older inpatients with chronic schizophrenia. We investigated the efficacy of individualized CR on the cognitive impairments of middle-aged or older inpatients with chronic schizophrenia within the context of comprehensive psychiatric rehabilitation (PR) by comparing the results obtained with PR only and treatment as usual (TAU). Method. Fifty-seven middle-aged and older individuals with chronic schizophrenia and mild to moderate cognitive deficits were enrolled. Thirty-eight who were undergoing PR were randomly assigned to CR + PR (N = 19) or PR-only (N = 19) groups. Nineteen participants who were undergoing TAU without CR or PR were evaluated pre- and post-treatment. Results. CR was easily provided and well received (drop-out rates = 5.3%) by middle-aged or older psychiatric inpatients. Compared to the PR-Only or TAU patients, patients in the CR + PR group showed greater improvement in executive functioning. Compared to TAU patients, CR + PR and PR-only patients showed greater improvement in logical memory. More patients in the CR + PR group improved clinically significantly in executive functioning and logical memory, compared with the PR-only and TAU patients. Conclusions. These results suggested that CR improved some cognitive deficits in middle-aged or older inpatients with chronic schizophrenia and that it was effective as an adjunctive treatment to the usual PR services provided in inpatient settings.